Strategi Manajemen SDM dan Bahasa Pemasaran bagi UMKM Desa Pugeran Kecamatan Gondang Kabupaten Mojokerto (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2026)
Micro, Small, and Medium Enterprises (MSMEs) of chips in Pugeran Village, Gondang District, Mojokerto Regency face structural obstacles in the form of limited internal governance and weak market penetration. Around 80% of business actors are still managed conventionally, triggering production inefficiencies and a lack of mastery of persuasive marketing language on packaging. This community service activity aims to reconstruct an effective division of labor based on HR governance mindset, build the capacity of practical skills in packaging copywriting and digital media, and change business behavior from conventional reactive to strategic proactive. The program is implemented with an Asset-Based Community Development (ABCD) approach through three main intervention stages, namely diagnosis and reconstruction of MSDM, co-creation and marketing language assistance, and the adoption of proactive behavior through coaching and market simulation. The results showed a significant socio-economic transformation, characterized by the implementation of labor division SOPs that increased production efficiency by 18%, as well as the adoption of new packaging and persuasive copywriting techniques that expanded market reach beyond the region and increased average turnover by 22% in two months. In addition, a new social institution was formed in the form of the "Prosperous Pugeran Chips Craftsmen Association" and the emergence of young local leaders as agents of the program's sustainability.